Pentingnya Edukasi Gizi Seimbang Pada Remaja di SMA Swasta Amanah Tahfidz - Sri Lasmawanti; Yaumil Hafsani Siregar; Hanny Ghafira; Agustin Elisabeth (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Adolescent health efforts aim to prepare adolescents to become healthy, intelligent, quality and productive adults and participate in maintaining, maintaining and improving their own health. Healthy Eating is a measure of the suitability of the subject's consumption with the recommended portion sizes of the Balanced Nutrition Guidelines. Maximum IGS means proving that the quality of food consumption is good and in accordance with the recommendations of the Balanced Nutrition Guidelines. In contrast to previous ages, entering the adolescent development stage, the child's daily nutritional adequacy rate (RDA) will automatically increase. According to WHO, teenagers are residents in the age range 10-19 years, according to the Republic of Indonesia Minister of Health Regulation Number 25 of 2014, teenagers are residents in the age range 10-18 years and according to the Population and Family Planning Agency (BKKBN) the age range for teenagers is 10-18 years. 24 years old and not married. The role of balanced nutrition education in teenagers' daily consumption is very necessary so that teenagers understand the nutritional intake needed by the body to support their growth and development from adolescence to adulthood, consuming a variety of foods with various types of food high in calories, protein, carbohydrates, minerals and vitamins to avoid disease and problems related to unbalanced nutrition.